Alkali-free glass substrate with high adhesive force to metal layer and preparation method and application of alkali-free glass substrate
By doping boron, aluminum, gallium, and indium elements on the alkali-free glass substrate, the problem of insufficient adhesion of the copper layer of the traditional alkali-free glass substrate is solved, and higher adhesion of metal layer and stability and reliability of electronic device manufacturing are achieved.
Patent Information
- Application Number
- CN202411935589.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-15
AI Technical Summary
The metal layer is insufficient when the traditional alkali-free glass substrate is coated with copper, which causes the copper layer to fall off easily during use, affecting the reliability and service life of the product.
By doping boron, aluminum, gallium, and indium elements on the alkali-free glass substrate, holes on the surface of the glass substrate are increased, and coordination bonds or ion bonds are promoted to form copper and its ions with the surface of the glass substrate, thereby improving the adhesion of the metal layer.
The adhesion between the metal layer and the glass substrate is significantly improved, the stability and reliability of copper-related processes in electronic device manufacturing are guaranteed, and the chemical and thermal stability of the glass substrate is maintained.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass, and in particular to an alkali-free glass substrate with high adhesion to a metal layer, and a preparation method and application thereof. Background Art
[0002] In the current electronic packaging and circuit board manufacturing fields, glass substrates are widely used due to their excellent physical and chemical properties, such as high flatness, high thermal conductivity, good insulation and corrosion resistance. However, traditional glass substrates face a key problem when plating metals such as copper: insufficient adhesion between the metal layer and the glass substrate. This is because: 1) Alkali-free glass substrates are mainly composed of elements such as silicon and oxygen bonded by covalent bonds, with a relatively stable structure and saturated chemical bonds; while it is difficult to form strong chemical bonds, such as covalent bonds or ionic bonds, between Cu and alkali-free glass substrates. The electronic structure and electronegativity of Cu atoms and atoms in glass are quite different, and it is not easy to transfer or share electrons to form stable chemical bonds, resulting in weak adhesion. 2) Lack of active sites: The surface of alkali-free glass substrates is relatively smooth and chemically stable, lacking active sites that can interact specifically with Cu. Unlike some material surfaces with specific functional groups or defects that can provide binding sites for Cu, alkali-free glass substrates are difficult to form effective chemical bonds with Cu, which limits the adhesion of Cu on their surfaces. This lack of adhesion can cause the metal layer to easily fall off during use, thus affecting the reliability and service life of the product.
[0003] In order to improve the adhesion between the metal layer and the glass substrate, the industry has conducted a lot of research and experiments. Possible methods include changing the surface properties of the glass substrate, such as increasing the surface roughness through chemical etching or physical grinding, using special adhesives, etc., to improve the adhesion of the metal layer. However, these methods often damage the surface of the glass substrate and affect its flatness, ultimately affecting the overall physical and chemical properties of the glass substrate.
[0004] Therefore, developing a new type of glass substrate that can not only maintain the original properties of the glass substrate but also significantly improve the adhesion of the metal layer is of great significance for promoting the development of the electronic packaging and circuit board manufacturing fields. Summary of the invention
[0005] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art, to provide an alkali-free glass substrate with high adhesion to the metal layer and a preparation method and application thereof, to dope the alkali-free glass substrate with boron, aluminum, gallium and indium elements, thereby increasing the adhesion of the metal on the surface of the glass substrate and ensuring the stability and reliability of copper-related processes in the manufacture of electronic devices.
[0006] The technical solution of the present invention is:
[0007] In a first aspect, the present invention provides an alkali-free glass substrate with high adhesion to a metal layer, comprising the following components in percentage by mass: SiO 2 60-78%, Al 2 O 3 10-17%, B 2 O 3 5-15%, BaO 1-3%, MgO 1-3%, CaO 2-5%, SrO 0.5-2%, ZnO 0.5-2%, SnO 2 0.1-1%; after the glass substrate is manufactured, it is doped, and the doping elements are boron, aluminum, gallium, and indium, wherein the mass ratio of boron, aluminum, gallium, and indium doping is (2-4):1:1:1, and the total doping concentration is 0.1-5at%.
[0008] In a second aspect, the present invention provides a method for preparing the above-mentioned alkali-free glass substrate with high adhesion to the metal layer. After the raw materials are mixed, they are melted, clarified, formed, annealed and element-doped in sequence, wherein the element-doping process is: placing the glass substrate in a doping furnace, introducing gas or steam containing boron, aluminum, gallium and indium elements, the doping temperature is 800-1000°C, and the doping time is 2.5-4h.
[0009] Preferably, the melting temperature is 1500-1650° C. and the melting time is 4-6 hours.
[0010] Preferably, the clarification temperature is 1600-1750° C. and the clarification time is 1.5-2.5 h.
[0011] Preferably, the molding temperature is 1000-1200°C.
[0012] Preferably, the annealing temperature is 500-650° C., and the annealing time is 1.5-2.5 h.
[0013] In a third aspect, the present invention provides an application of the above-mentioned alkali-free glass substrate with high adhesion to the metal layer. The alkali-free glass substrate is used in the fields of printed circuit boards, flat panel displays, and semiconductor packaging to improve the adhesion between the metal layer and the alkali-free glass substrate and ensure the stability and reliability of related processes in the manufacture of electronic devices.
[0014] Compared with the prior art, the present invention has the following beneficial effects:
[0015] 1. The present invention dopes the alkali-free glass substrate with boron, aluminum, gallium and indium elements, so that a large number of holes are formed on the surface of the glass substrate, and then copper and its ions or other metals with certain oxidizability on the surface of the glass substrate can easily obtain electrons therefrom, and form chemical bonds such as coordination bonds or ionic bonds with the holes; and charge transfer and electrostatic effects can also be generated (holes exist near the top of the valence band on the surface of the doped glass substrate, and their Fermi level is relatively low. When contacting with copper and its ions or other metals with certain oxidizability, the electron cloud of the metal will transfer charge with the holes on the surface of the doped glass substrate, and the metal atoms will transfer part of the electrons to the holes on the glass surface, forming a certain electrostatic attraction), thereby increasing the adhesion of the metal on the surface of the glass substrate, and ensuring the stability and reliability of copper-related processes in the manufacture of electronic devices.
[0016] 2. The alkali-free glass substrate of the present invention has good chemical stability: the main components and proportions enable it to resist chemical corrosion such as acid and alkali, maintain stable structure and performance in the chemical environment of electronic manufacturing, and do not affect its adhesion to metal. Excellent thermal stability: precise high-temperature process treatment gives the glass substrate the ability to withstand the high-temperature links of electronic device processing, and it matches the metal stress well during thermal expansion and contraction to maintain adhesion. High mechanical strength: specific components and processes enable it to withstand external force impacts, provide support for copper circuits, etc., and reduce the risk of copper layer peeling due to mechanical factors. The glass substrate of the present invention can achieve higher quality copper circuits or connections in electronic fields such as printed circuit boards, flat panel displays, and semiconductor packaging, and promote the development of high-performance, miniaturized electronic devices.
[0017] 3. The present invention is compatible with existing processes. The preparation method of the present invention is similar to the traditional glass substrate production process steps, and only the parameters are optimized. There is no need for enterprises to significantly update equipment and process systems. It is easy to promote and apply, reduce costs and difficulty of technical transformation, and promote industrialization. DETAILED DESCRIPTION
[0018] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0019] Example 1
[0020] The method for preparing the alkali-free glass substrate of this embodiment comprises the following steps:
[0021] (1) Glass raw material mixing: weigh the raw materials according to the following mass percentages: SiO 2 65%、Al 2 O 3 15.5%, B 2 O 3 10%, BaO 2%, MgO 2%, CaO 3%, SrO 1%, ZnO 1%, SnO2 0.5%; mix the raw materials in a mixer for 55 minutes;
[0022] (2) Melting: The mixed raw materials are put into a glass melting furnace and melted at 1550°C for 6 hours, stirring evenly to fully melt the raw materials and form a highly uniform glass liquid;
[0023] (3) Clarification: Clarification at 1650°C for 2.5 hours effectively removes bubbles and tiny impurities in the glass liquid, improving the purity and transparency of the glass;
[0024] (4) Molding: The glass liquid is molded into a glass substrate using float molding at a molding temperature of 1050°C to ensure that the glass substrate has excellent flatness and uniform thickness;
[0025] (5) Annealing: The formed glass substrate is annealed in an annealing furnace at 580° C. for 2.5 h to effectively eliminate the stress generated inside the glass substrate during the forming process and enhance its mechanical strength and stability;
[0026] (6) Doping: The annealed glass substrate is placed in a doping furnace, and aluminum trichloride vapor, gallium trichloride vapor, boron trichloride vapor and indium trichloride vapor are introduced, wherein the mass ratio of doped boron, aluminum, gallium and indium is 2:1:1:1, the doping temperature is 900°C, the doping time is 3.5 h, and the doping concentration is 1 at %, so that the doping elements diffuse into a certain depth on the surface of the glass substrate, thereby generating a large number of holes on the surface of the glass substrate.
[0027] The copper adhesion test of the obtained glass substrate was carried out. The copper film was plated on the glass substrate by the cross-cut method, and then the cross-cut was crossed with a cross-cut tool, and then the copper film was pasted and torn off with tape to observe the shedding of the copper film. The results showed that the shedding area of the copper film was 0.47%, indicating that the copper and the glass substrate had extremely high adhesion.
[0028] Example 2
[0029] The method for preparing the alkali-free glass substrate of this embodiment comprises the following steps:
[0030] (1) Glass raw material mixing: weigh the raw materials according to the following mass percentages: SiO 2 60%、Al 2 O 3 16%, B 2 O 3 13%, BaO 2.5%, MgO 2%, CaO 4%, SrO 1%, ZnO 1%, SnO 2 0.5%; mix the raw materials in a mixer for 55 minutes;
[0031] (2) Melting: Put the raw materials into a glass melting furnace, melt them at 1500°C for 4 hours, and stir them evenly;
[0032] (3) Clarification: Clarify at 1600°C for 1.5h;
[0033] (4) Molding: Float molding is adopted, and the molding temperature is 1000℃;
[0034] (5) Annealing: annealing the formed glass substrate in an annealing furnace at 500° C. for 1.5 h;
[0035] (6) Doping: The annealed glass substrate is placed in a doping furnace and a mixed vapor containing aluminum, gallium, boron and indium is introduced, wherein the mass ratio of doped boron, aluminum, gallium and indium is 3:1:1:1, the doping temperature is 800°C, the doping time is 2.5 h, and the doping concentration is 0.1 at%.
[0036] The copper adhesion test of the obtained glass substrate was carried out by using the cross-hatch method, and the copper film peeling area was less than 1.3%, indicating that the copper had extremely high adhesion to the glass substrate.
[0037] Example 3
[0038] The method for preparing the alkali-free glass substrate of this embodiment comprises the following steps:
[0039] (1) Mixing glass raw materials: Weigh the raw materials according to the following mass percentages: SiO 2 78%, Al 2 O 3 10%, B 2 O 3 5%, BaO 1%, MgO 1%, CaO 2.5%, SrO 1%, ZnO 1%, SnO 2 0.5%; mix the raw materials in a mixer for 55 minutes;
[0040] (2) Melting: Put the raw materials into a glass melting furnace, melt them at 1650°C for 6 hours, and stir them evenly;
[0041] (3) Clarification: Clarify at 1750°C for 2.5h;
[0042] (4) Molding: Float molding is adopted, and the molding temperature is 1200℃;
[0043] (5) Annealing: annealing the formed glass substrate in an annealing furnace at 650° C. for 2.5 h;
[0044] (6) Doping: The annealed glass substrate is placed in a doping furnace and a mixed vapor containing aluminum, gallium, boron and indium is introduced, wherein the mass ratio of doped boron, aluminum, gallium and indium is 4:1:1:1, the doping temperature is 1000°C, the doping time is 4 h, and the doping concentration is 5 at%.
[0045] The copper adhesion test of the obtained glass substrate was carried out by using the cross-hatch method, and the copper film peeling area was less than 0.9%, indicating that the copper and the glass substrate had extremely high adhesion.
[0046] Comparative Example 1
[0047] The difference from Example 1 is that step (6) is not performed.
[0048] The glass substrate prepared in Comparative Example 1 was tested for copper adhesion. After the cross-hatch method was used, the copper film peeling area reached 75%, indicating that the glass substrate without element doping treatment had poor adhesion to copper.
[0049] Comparative Example 2
[0050] The difference from Example 1 is that in step (6), only boron trichloride vapor is introduced.
[0051] The glass substrate prepared in Comparative Example 2 was subjected to a copper adhesion test. After the cross-hatch method was used, the copper film peeling area was 14.7%, indicating that the adhesion between copper and the glass substrate was insufficient.
[0052] Comparative Example 3
[0053] The difference from Example 1 is that in step (6), only aluminum trichloride vapor, gallium trichloride vapor and indium trichloride vapor are introduced.
[0054] The glass substrate prepared in Comparative Example 3 was subjected to a copper adhesion test. After the cross-hatch method was used, the copper film peeling area was 19.4%, indicating that the adhesion between copper and the glass substrate was insufficient.
[0055] Comparative Example 4
[0056] The difference from Example 1 is that in step (6), only sodium chloride vapor is introduced.
[0057] The glass substrate prepared in Comparative Example 4 was tested for copper adhesion. After the cross-hatch method, the copper film peeling area was 77%. This was because the inappropriate element sodium was doped and a structure conducive to combining with copper could not be formed, resulting in poor adhesion of the glass substrate to copper.
[0058] Comparative Example 5
[0059] The difference from Example 1 is that in step (6), the mass ratio of doped boron, aluminum, gallium and indium is 1:2:2:1.
[0060] The glass substrate prepared in Comparative Example 5 was tested for copper adhesion. After the cross-hatch method was used, the copper film fell off in an area of 13%, indicating that the glass substrate had insufficient adhesion to copper. This is because when the element doping ratio is appropriate, boron can form a large number of holes, while aluminum, gallium, and indium play an auxiliary role in stabilizing the glass structure and adjusting the charge distribution. When the surface of the glass substrate is in contact with metals such as copper, the electrons of copper ions or atoms can more easily enter the holes formed by boron. At the same time, the charge distribution and stable glass structure adjusted by aluminum, gallium, and indium help to maintain the formation and stability of this chemical bond. Therefore, when the doping ratio of boron is too low, the number of holes is insufficient, and metals such as copper cannot effectively form sufficient chemical bonds with the glass surface, resulting in poor adhesion; relatively speaking, if the doping ratio of aluminum, gallium, and indium is too high, it will affect the efficiency of boron forming holes, and may also cause the glass structure to be too complex, which is not conducive to the adsorption and bonding of metals.
[0061] Comparative Example 6
[0062] The difference from Example 1 is that in step (6), the doping concentration is 0.05 at %.
[0063] The glass substrate prepared in Comparative Example 6 was tested for copper adhesion. After the cross-hatch method was used, the copper film peeling area was about 57%, indicating that the element doping amount was too small and sufficient holes could not be formed, resulting in poor adhesion of the glass substrate to copper.
[0064] Comparative Example 7
[0065] The difference from Example 1 is that in step (6), the doping concentration is 8 at %.
[0066] The glass substrate prepared in Comparative Example 6 was tested for copper adhesion. After the cross-hatch method was used, the glass shattered, indicating that excessive element doping would cause the structure of the glass substrate to be destroyed, making it brittle even under a small external force.
[0067] Comparative Example 8
[0068] The difference from Example 1 is that in step (6), the doping temperature is 650°C.
[0069] The copper adhesion test was conducted on the glass substrate prepared in Comparative Example 6. After the cross-hatch method, the copper film peeling area reached 23%. This is because the element doping temperature is too low, and the doping element fails to effectively diffuse into the surface of the glass substrate to form sufficient holes, resulting in reduced adhesion of the glass substrate to copper.
Claims
1. An alkali-free glass substrate having high adhesion to a metal layer, characterized in that: The invention comprises the following components in mass percentage: SiO2 60-78%, Al2O3 10-17%, B2O3 5-15%, BaO 1-3%, MgO 1-3%, CaO 2-5%, SrO 0.5-2%, ZnO 0.5-2%, SnO2 0.1-1%; after the glass substrate is manufactured, a doping treatment is performed, wherein the doping elements are boron, aluminum, gallium, and indium, wherein the mass ratio of boron, aluminum, gallium, and indium doping is (2-4):1:1:1, and the total doping concentration is 0.1-5at%.
2. The method for preparing an alkali-free glass substrate having high adhesion to a metal layer according to claim 1, characterized in that: After the raw materials are mixed, they are melted, clarified, formed, annealed and doped with elements in sequence. The element doping process is as follows: placing the glass substrate in a doping furnace, introducing gas or steam containing boron, aluminum, gallium and indium elements, the doping temperature is 800-1000°C, and the doping time is 2.5-4h.
3. The method for preparing an alkali-free glass substrate having high adhesion to a metal layer according to claim 2, characterized in that: The melting temperature is 1500-1650°C and the melting time is 4-6h.
4. The method for preparing an alkali-free glass substrate having high adhesion to a metal layer according to claim 2, characterized in that: The clarification temperature is 1600-1750℃, and the clarification time is 1.5-2.5h.
5. The method for preparing an alkali-free glass substrate having high adhesion to a metal layer according to claim 2, characterized in that: The molding temperature is 1000-1200℃.
6. The method for preparing an alkali-free glass substrate having high adhesion to a metal layer according to claim 2, characterized in that: The annealing temperature is 500-650°C and the annealing time is 1.5-2.5h.
7. The use of the alkali-free glass substrate having high adhesion to the metal layer as claimed in claim 1, characterized in that: The alkali-free glass substrate is used in the fields of printed circuit boards, flat panel displays, and semiconductor packaging.